2011
DOI: 10.1007/s12194-011-0122-5
|View full text |Cite
|
Sign up to set email alerts
|

From PACS to Web-based ePR system with image distribution for enterprise-level filmless healthcare delivery

Abstract: The concept of PACS (picture archiving and communication system) was initiated in 1982 during the SPIE medical imaging conference in New Port Beach, CA. Since then PACS has been matured to become an everyday clinical tool for image archiving, communication, display, and review. This paper follows the continuous development of PACS technology including Web-based PACS, PACS and ePR (electronic patient record), enterprise PACS to ePR with image distribution (ID). The concept of large-scale Web-based enterprise PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…As elaborated by previous researchers ( 12 , 13 ), data compression can impact PACS, both in short-term and long-term data, and it can reduce the file size for exchange among users. Although this could negatively impact the quality of images, the rate and method of image compression were addressed in this review and included in the PACS evaluation protocol.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…As elaborated by previous researchers ( 12 , 13 ), data compression can impact PACS, both in short-term and long-term data, and it can reduce the file size for exchange among users. Although this could negatively impact the quality of images, the rate and method of image compression were addressed in this review and included in the PACS evaluation protocol.…”
Section: Discussionmentioning
confidence: 87%
“…Other studies ( 12 , 18 , 19 ), have strongly suggested the use of such system network as client servers or web-based architecture, using ATM, Ethernet and/or TCP/IP protocols. Hence the inclusion of these network elements in our PACS evaluation protocol among the essential prerequisites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Manipulating interactive remote visualizations via web-based systems that are similar to modern hospital information systems would enhance the accessibility even further 3. We assert that a system that uses only standard web browsers with no added software provides universal access to remote visualization with highest client mobility.…”
Section: Objectivementioning
confidence: 95%